Expert system for identification of natural enemies of tobacco pests - Ravisankar, H; Rao, S Gunneswara; Sreedhar, U (Indian Journal of Plant Protection, 2020)
Insect pests are one of the important constraints in production and storage of quality tobacco. Identification of insect pests and their natural enemies (biocontrol agents) is one of the important aspects in integrated pest management (IPM). Identification of natural enemies of tobacco insect pests involves recognition and the stage at which the natural enemies attack the pest. Based on this, an expert system was developed for identification of natural enemies and disease symptoms caused by entomopathogens on tobacco insect pests. Using this system, user can access information available on the natural enemies, their potential in controlling a specific pest and impact of pesticides on the natural enemies. This system provides information on biocontrol agents of tobacco insect pests and their use at proper stage of the pests to scientists, extension workers involved in agriculture development, farmers and students. Using this system one can identify the major insect pests and their biocontrol agents for effective decision making in insect pest management in tobacco and to adopt good agricultural practices. It will help the clientele in decision making to integrate biocontrol agents in IPM of tobacco.